Factors affecting the interval between marriage and first birth using the Cox regression model - Abbas Rahimiforoushani; Maryam Kazemi; Amin Ghanbarnejad; Mohammad Reza Eshraghian; Fereshte Majlesi (حیات, 2016)
Background & Aim: Fertility is the most important factors affecting population fluctuations. Reproductive behaviors of a community can be studied through different methods. One of the methods is the evaluation of the interval between marriage and the birth of the first child. The aim of this study was to investigate the factors influencing the interval between marriage and first birth using the Cox regression model.